MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) - Dewi Latifah; Sukanto Sukandar Madio (Mosharafa: Jurnal Pendidikan Matematika, 2014)
Abstract:Mathematics is a universal science that underlies the development of technology and have an important role in advancing the human intellect. Problem solving is the focus in the study of mathematics as a problem solving type of learning that most high level and complex. Quasi-experimental study with Nonequivalent Group Pre-test Post-test Design aims to determine the increase in mathematical problem solving ability of student who get Missouri Mathematics Project (MMP) learning model better than students who received conventional learning models, and how the increase in mathematical problem solving ability of students who get the Missouri Mathematics Project (MMP) learning model, as well as students toward learning model Missouri Mathematics Project (MMP). Sampel population in this were students MAN at Garut. The results showed that: (1) Increase in mathematical problem solving ability of student who get Missouri Mathematics Project (MMP) learning model better than students who received conventional learning models, (2) Improvement of students mathematical problem solving abilities that get being interpreted Missouri Mathematics Project (MMP) learning model, (3) Students attitudes toward learning model Missouri Mathematics Project (MMP) interpreted very positive. Abstrak:Matematika merupakan ilmu yang universal yang mendasari perkembangan teknologi dan mempunyai peran penting dalam memajukan daya pikir manusia. Pemecahan masalah merupakan fokus dalam pembelajaran matematika karena pemecahan masalah tipe belajar yang tingkatnya paling tinggi dan kompleks. Penelitian kuasi eksperimen dengan Nonequivalent Group Pre-test Post-test Design ini bertujuan untuk mengetahui peningkatan kemampuan pemecahan masalah matematis siswa yang mendapatkan model pembelajaran Missouri Mathematics Project (MMP) lebih baik dari siswa yang mendapatkan model pembelajaran konvensional, dan bagaimana peningkatan kemampuan pemecahan masalah matematis siswa yang mendapatkan model pembelajaran Missouri Mathematics Project (MMP), serta sikap siswa terhadap model pembelajaran Missouri Mathematics Project (MMP). Sampel populasi dalam penelitian ini adalah siswa MAN di Garut. Hasil Penelitian menunjukkan bahwa: (1) Peningkatan kemampuan pemecahan masalah matematis siswa yang mendapatkan model model pembelajaran Missouri Mathematics Project (MMP) lebih baik dari siswa yang mendapatkan pembelajaran konvensional, (2) Peningkatan kemampuan pemecahan masalah matematis siswa yang mendapatkan model pembelajaran Missouri Mathematics Project (MMP) diinterprestasikan sedang, (3) Sikap siswa terhadap model pembelajaran Missouri Mathematics Project (MMP) diinterprestasikan sangat positif.